Pengaruh Motivasi dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Pabrik Kelapa Sawit Cikasungka PT. Perkebunan Nusantara VIII Bogor - Texa Lima Dwi; Slamet Abadi; Suhaeni Suhaeni (Jurnal Ilmiah Wahana Pendidikan, 2022)
Motivation is an encouragement in a person who comes from inside or outside himself to do work with the spirit of using his abilities and skills to achieve organizational goals. The work environment is an important place to create a related work relationship between people who are in their environment regarding physical, social and psychological life in the company that will affect employee performance and productivity. Motivation and a good work environment will result in good performance. The purpose of this study is to determine the influence of motivation and work environment on the performance of employees of Pabrik Kelapa Sawit (PKS) Cikasungka PT. Perkebunan Nusantara VIII Bogor plantations partially and simultaneously. The location of this research is the Pabrik Kelapa Sawit (PKS) Cikasungka PT. Perkebunan Nusantara VIII Bogor Plantation. This research method uses quantitative research methods with a descriptive approach. Data analysis techniques using MSI classical assumption test, multiple linear regression test, f test and t test. The results of this study are (1) motivation partially affects the significance of employee performance and the work environment partially affects employee performance. (2) Motivation and work environment affect simultaneously on employee performance. Conclusion The work environment also has a significant influence on the performance of employees significantly on the performance of employees at Pabrik Kelapa Sawit (PKS) Cikasungka PT. Perkebunan Nusantara VIII Bogor.Motivation and work environment together have a significant influence on employee performance at Pabrik Kelapa Sawit (PKS) Cikasungka PT. Perkebunan Nusantara VIII Bogor. Motivation significantly has a significant influence on the performance of employees at Pabrik Kelapa Sawit (PKS) Cikasungka PT. Perkebunan Nusantara VIII Bogor.